КОМПЬЮТЕРНОЕ МОДЕЛИРОВАНИЕ ТЕПЛОВЫХ ПРОЦЕССОВ В ОДНОФАЗНОМ ТРАНСФОРМАТОРЕ С УЧЕТОМ АНИЗОТРОПИИ ТЕПЛОВЫХ СВОЙСТВ АКТИВНЫХ ЭЛЕМЕНТОВ - Кучерявая, И.Н. (Інститут електродинаміки НАН України, Київ, 2013)
The mathematical model and computer technique are developed to compute and study the thermal processes in a transformer taking into account the anisotropic heat conductivity of materials for active elements – magnetic core and windings. The created computing facilities provide a possibility to simulate two methods of transformer cooling – on the basis of free air convection and with the use of the external forced cooling by fan. Such two cooling conditions are investigated on the example of single-phase transformer with shell-type core. The decrease of temperature is shown in the case of forced cooling as compared to the natural cooling of the transformer. The developed computer facilities can be used for transformer design, study of different regimes and monitoring of transformer operation. References 19, tables 2, figures 4.